2021
DOI: 10.2196/26073
|View full text |Cite
|
Sign up to set email alerts
|

Protective Behaviors and Secondary Harms Resulting From Nonpharmaceutical Interventions During the COVID-19 Epidemic in South Africa: Multisite, Prospective Longitudinal Study

Abstract: Background In March 2020, South Africa implemented strict nonpharmaceutical interventions (NPIs) to contain the spread of COVID-19. Over the subsequent 5 months, NPI policies were eased in stages according to a national strategy. COVID-19 spread throughout the country heterogeneously; the disease reached rural areas by July and case numbers peaked from July to August. A second COVID-19 wave began in late 2020. Data on the impact of NPI policies on social and economic well-being and access to health… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…Unsurprisingly, we found that time spent at home rose, while shared person-time spent in other homes dropped by 89% and at ‘other locations’ (largely school, work and shops) by 94%. This reduced potential for exposure in both public and private suggests that people are following rules both when they can and cannot be seen; these data are also consistent with other evidence from this area of reduced mobility in July and August compared even to earlier in 2020 [ 31 ]. Our respondents reported similar time spent attending health clinics in the two years, but reported that fewer others were present when they attended in 2020, perhaps reflecting improved social distancing policies within clinics.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Unsurprisingly, we found that time spent at home rose, while shared person-time spent in other homes dropped by 89% and at ‘other locations’ (largely school, work and shops) by 94%. This reduced potential for exposure in both public and private suggests that people are following rules both when they can and cannot be seen; these data are also consistent with other evidence from this area of reduced mobility in July and August compared even to earlier in 2020 [ 31 ]. Our respondents reported similar time spent attending health clinics in the two years, but reported that fewer others were present when they attended in 2020, perhaps reflecting improved social distancing policies within clinics.…”
Section: Discussionsupporting
confidence: 87%
“…Under the assumptions that close interaction contacts are the most important for infection transmission, and qualitatively the same in both years, we estimate a 42–45% reduction in the likely basic reproduction number between the two surveys. Given the substantial level of use of face coverings outside the home required and observed in South Africa [ 31 ], this reduction is likely to be an underestimate.…”
Section: Discussionmentioning
confidence: 99%
“…While there appeared to be some hesitancy in accessing care due to the pandemic, health care service avoidance as a result of COVID-19 was not widely reported in the cohort. The South African Population Research Infrastructure Network (SAPRIN) observed stable levels of chronic medication use within the Agincourt and DIMAMO (Limpopo) HDSS during the first wave of the pandemic; however, in the Africa Health Research Institute HDSS site in KwaZulu Natal, the extent of missed medication was significant ( Harling et al, 2021 ). This suggests local variations in interruptions in health service use.…”
Section: Discussionmentioning
confidence: 99%
“…Further, elevated blood pressure is increasing mortality for men and women. At present, the Agincourt HDSS is collecting data on COVID-19 in its surveillance site [ 44 ]. Future studies need to take into consideration the impacts of this third epidemic and its interactions with the advanced HIV and hypertension epidemics that continue to affect the lives of rural South Africans.…”
Section: Discussionmentioning
confidence: 99%